2007
DOI: 10.1371/journal.pone.0000195
|View full text |Cite
|
Sign up to set email alerts
|

Is the Prevalence of Overactive Bladder Overestimated? A Population-Based Study in Finland

Abstract: BackgroundIn earlier studies, one in six adults had overactive bladder which may impair quality of life. However, earlier studies have either not been population-based or have suffered from methodological limitations. Our aim was to assess the prevalence of overactive bladder symptoms, based on a representative study population and using consistent definitions and exclusions.Methodology/Principal FindingsThe aim of the study was to assess the age-standardized prevalence of overactive bladder defined as urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…of urgency/OAB (17). Based on a random sample of the Finnish population register, they aimed at obtaining an unbiased estimate of the prevalence of urgency/OAB and concluded that the prevalence amongst male adults aged 18-79 years was 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…of urgency/OAB (17). Based on a random sample of the Finnish population register, they aimed at obtaining an unbiased estimate of the prevalence of urgency/OAB and concluded that the prevalence amongst male adults aged 18-79 years was 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…15 In adults this figure was higher, at 6%, which is similar to the findings of a recent study of Finnish adults. 17 Urinary urgency was the most common symptom in children. The prevalence of occasional urge symptoms up to adulthood corresponds with the findings of Tikkinen et al of approximately 45% mild and 5% moderate/severe urgency in healthy Finnish males 18 to 57 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OAB was 11.8% (similarly in men and women) [2] . Tikkinen et al [7] mentioned a prevalence of OAB of 6.5% (5.6% after excluding a man with infravesical obstruction).…”
Section: Discussionmentioning
confidence: 99%